Satisfaction of the students in a preparatory course of mathematics in e-modalities - Carolina Hernández Gutiérrez; Manuel Juárez Pacheco (Universidad de Guadalajara, 2018)
The aim of this work was to analyze student satisfaction with a preparatory course in advanced mathematics, in e-learning and b-learning modalities, in a master's degree in electronics, in a graduate institution of the National Technological of Mexico. The satisfaction analysis was carried out based on the Disconfirmation of Expectations Theory and the categories for the analysis were taken from the Theory of Didactic Suitability. The research was designed as a case study, with exploratory and descriptive scope. To carry out the assessment of student satisfaction, two online questionnaires were applied, one before starting the course to know their expectations and another at the end to assess satisfaction. Semi-structured interviews were conducted with the students and the teacher who taught the course and non-participant observation was carried out during the e-learning modality, for data triangulation. Although the study was carried out with only one group, the preliminary results show that the students, despite the material and affective limitations during the course, have a high degree of satisfaction with it. The categories of analysis are suitable for analysis of math courses in these modalities.